2022
DOI: 10.1002/oby.23499
|View full text |Cite
|
Sign up to set email alerts
|

Time–restricted eating alters the 24‐hour profile of adipose tissue transcriptome in men with obesity

Abstract: Objective: Time-restricted eating (TRE) restores circadian rhythms in mice, but the evidence to support this in humans is limited. The objective of this study was to investigate the effects of TRE on 24-hour profiles of plasma metabolites, glucoregulatory hormones, and the subcutaneous adipose tissue (SAT) transcriptome in humans. Methods: Men (n = 15, age = 63 [4] years, BMI 30.5 [2.4] kg/m 2 ) were recruited. A 35-hour metabolic ward stay was conducted at baseline and after 8 weeks of 10-hour TRE. Assessment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 59 publications
0
14
0
2
Order By: Relevance
“…136 Similarly, in humans, TRE in form of the religious daytime dry fasting (whereas food is consumed in the night) showed impacts on the circadian system, advancing the circadian phase in blood monocytes by 1.1 h. 137 Another trial on 10-h daytime eating restriction revealed that TRE restores the 24-h profile of adipose tissue transcriptome including rhythms of core clock genes in obese men. 138 Furthermore, TRE trials demonstrated improvements in glucose regulation, insulin sensitivity, blood lipid levels, blood pressure, oxidative stress markers, and quality of life measures, although the effects may differ between early and midday/late eating windows. [139][140][141][142] Some studies showed that TRE affects the gut microbiome, which might contribute to the described metabolic effects of TRE.…”
Section: Future Directions: Dietary Approaches As a Chron Obi Olo Gic...mentioning
confidence: 99%
“…136 Similarly, in humans, TRE in form of the religious daytime dry fasting (whereas food is consumed in the night) showed impacts on the circadian system, advancing the circadian phase in blood monocytes by 1.1 h. 137 Another trial on 10-h daytime eating restriction revealed that TRE restores the 24-h profile of adipose tissue transcriptome including rhythms of core clock genes in obese men. 138 Furthermore, TRE trials demonstrated improvements in glucose regulation, insulin sensitivity, blood lipid levels, blood pressure, oxidative stress markers, and quality of life measures, although the effects may differ between early and midday/late eating windows. [139][140][141][142] Some studies showed that TRE affects the gut microbiome, which might contribute to the described metabolic effects of TRE.…”
Section: Future Directions: Dietary Approaches As a Chron Obi Olo Gic...mentioning
confidence: 99%
“…Recent human studies have confirmed that TRE decreases genes involved in mitochondrial regulation [54] and strengthens circadian clock gene rhythms [55] in subcutaneous adipose tissue. Additionally, transcriptomic analyses have identified transcriptional regulation, small guanosine‐5'‐triphosphatease (GTPase) binding, and proteasome function as key pathways modulated by TRE [54, 55]. Thus, TRE has tremendous therapeutic potential to normalize the metabolic rhythms disrupted in metabolic disorders through many potential mechanisms, broadening its potential impact (Figure 1).…”
Section: Circadian Rhythms and Trf/trementioning
confidence: 99%
“…Additionally, transcriptomics comparing TRF with ALF have identified several pathways modified by TRF that could contribute to its beneficial effects, including clock genes, molecular chaperone T-complex protein ring complex (TRiC)/chaperonin containing T-complex protein 1 (CCT) complex, which is upregulated by TRF, and mitochondrial electron transport chain components, which are downregulated by TRF [3,31]. Recent human studies have confirmed that TRE decreases genes involved in mitochondrial regulation [54] and strengthens circadian clock gene rhythms [55] in subcutaneous adipose tissue. Additionally, transcriptomic analyses have identified transcriptional regulation, small guanosine-5'-triphosphatease (GTPase) binding, and proteasome function as key pathways modulated by TRE [54,55].…”
Section: Trf/trementioning
confidence: 99%
“…Interessant war zudem, dass die Spätesser vermehrt dem "Abendtypus" zugeordnet werden konnten, die nachts länger wachbleiben, morgens später aufstehen und ihre beste kognitive und physische Leistungsfähigkeit am späteren Nachmittag oder Abend aufweisen, und häufiger die Risikovariante CLOCK rs4580 704 trugen [3]. TRE scheint das Potenzial zu haben, ein chrononutritives Instrument zu sein, welches veränderte zirkadiane Rhythmen wiederherzustellen vermag [4]. Es wird vermutlich aber kein für alle Personen gültiges TRE-Schema nach dem Motto "one size fits all" geben.…”
unclassified
“…TRE scheint das Potenzial zu haben, ein chrononutritives Instrument zu sein, welches veränderte zirkadiane Rhythmen wiederherzustellen vermag 4 . Es wird vermutlich aber kein für alle Personen gültiges TRE-Schema nach dem Motto „one size fits all“ geben.…”
unclassified